Efek Vinil Klorida terhadap Metilasi DNA: Tinjauan Sistematis - Nabila Azzahra Alifia; Abdul Rohim Tualeka (Universitas Airlangga, 2023)
Background: Vinyl chloride (VC) is a toxic chemical hazard which is characterized with colorless gas widely used in the plastics manufacturing industry. Vinyl chloride (VC) has various health threatening effects such as bothering deoxyribonucleic acid (DNA) methylation that can cause hepatocellular carcinoma (HCC) and cancer. Objectives: The purpose of writing systematic review is to determine the effect vinyl chloride (VC) to deoxyribonucleic acid (DNA) methylation. Methods: The research design is a systematic review article using PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. This question is structured by taking into account 4 stages, namely: Population, Intervention, Comparison, and Outcome (PICO). By searching for articles/journals that match the keywords in PICO, namely